Modern contraceptive discontinuation and associated factors among adolescent girls and young women in Tanzania: An analysis of a nationally representative data - Victoria J Solomon; Shadrack E Kibona; Elevatus N Mukyanuzi; Christopher H Mbotwa (Women's Health)
Background: Contraceptive use is vital in reducing the risk of unintended pregnancies and early motherhood. Despite the well-established benefits, the uptake of modern contraceptive methods among adolescent girls and young women (AGYW) is sub-optimal in sub-Saharan Africa. Furthermore, the discontinuation rate of modern contraceptive use poses a significant challenge to its effectiveness. Objective: We aimed to determine a 12-month modern contraceptive discontinuation rate, reasons for discontinuation, and associated factors among AGYW in Tanzania. Design: Retrospective nested within the cross-sectional utilizing quantitative approach. Methods: We retrospectively analysed calendar data on contraceptive use collected in the 2022 Tanzania Demographic and Health Survey (2022 TDHS). The 2022 TDHS data collection was implemented between February and July 2022. The study population comprised AGYW aged 15–24 years. The unit of analysis was the contraceptive episode of use, defined as the period between the start of use and the termination of the method. Our analysis was mainly based on the discontinuation due to dissatisfaction with the method. We used a life-table method to estimate the contraceptive discontinuation rates. A frailty model was employed to assess the factors associated with the discontinuation rate. Results: A total of 668 AGYW with a mean (±standard deviation) age of 21.5 ± 2.1 years were included in the analysis. The overall prevalence of 12-month discontinuation rate due to dissatisfaction with the method was 32.3%. Higher discontinuation rates were observed among injectable and pills. The main reasons for discontinuation were side effects (13.7%) and change in menstrual cycle (8%). Factors associated with higher discontinuation rates included higher age (adjusted hazard ratio (aHR) 1.64, 95% confidence interval (CI) 1.06–2.51 for the 20–24 age group), residing in households headed by a female (aHR 1.40, 95% CI 1.05–1.85), and residing in the western zone (aHR 1.87, 95% CI 1.21–2.90). Conclusion: This study revealed a high prevalence rate of modern contraceptive discontinuation among AGYW in Tanzania. The management of side effects needs to be incorporated into programs aimed at promoting the sustained use of modern contraceptive methods.